PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, WHISTLEBLOWING SYSTEM, DAN MORALITAS INDIVIDU TERHADAP PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN KEUANGAN DESA - I Made Hangga Hariawan; Ni Komang Sumadi; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2020)
Prevention of fraud (fraudi) is an act or an effort to prevent or detain a person from not doing an act of fraud which is found to be detrimental. This study aims to determine the effect of competence in human resources, whistleblowingi systemi and individual morality in the face of preventive fraud (fraudi) in managing the financial management of Desai in Desai in Klungkung District. This research was conducted in all Desai offices in Klungkung District. With a total sample of 87 Desai apparatus, the sampling method used was purposive sampling. Data analysis techniques used in this research are Descriptive Statistics, Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, Determination Coefficient, F Test and T Test. The results of the study show that the competence of human resources does not affect the prevention of fraud (fraudi). Whistleblowingi systemi positively influences the prevention of fraud (fraudi). Individual morality has a positive effect on preventing fraud (fraudi).